Language and linguistics in journalism - محوی, محمدي محوي (Sulaimani Journal for Humanities, 2000)
Linguistics in general media is specialisation in the grammatical components „Syntax, Morphology, Phonology and Semantics“ with a full knowledge in the orthography of that language, which is based on the above components. The right use of those specific sciences with the appropriate events, subjects, place and time of the events and the best chosen of the language of different levels assure the journalist's success. Chanel-development is the development of technic and language. Language is also one of the basic components of the media-development. We mean by the term „language“ the spoken and written language. For the journalism aims we distinguish between the written language of magazins, newspapers and scientific books. Journalist is an intellectual writer, who motivated people and tries to moove them to general changes. Generally he uses the standard high written language. The underlying level of the spoken language is chosen as a basic of standard language. Till now we are used to use South-Kurdish as a standard language for the whole kurds in IrakiKurdistan. Beside this dialect, as an official language of journalism, journalist is in need to have a good knowledge in sociolinguistics. The language of journalism is directly affected by the theories of media. Other aspects have great affects on the language of journalism, which are outside of language -language external affects-. The affect of these factors depend on other language external factors, such as change in live and media.